Adoption of Clear Convincing Evidence in Hong Kong - Chen, Max Hua (American Journal of Trade and Policy, 2022)
Drawing from overseas practices, namely the law in England & Wales (E&W) and the law in the United States (US), this article will critically discuss whether a higher standard of proof of ‘clear and convincing evidence (CCE) should be adopted in non-criminal proceedings in Hong Kong (HK), and if so, in what types of cases. Consequently, because the 'balance of probabilities ("BOP") and 'beyond reasonable doubt' ('BRD') standards have themselves proved to be highly complex, and jurors have found these standards even more complicated to understand, the introduction of an intermediate CCE standard would invariably lead to even more complexity and misunderstanding in the current HK evidentiary system applicable to non-criminal proceedings. This is precisely the opposite of what the HK evidentiary system needs now. Whilst a higher CCE standard of proof could in principle be adopted within HK, for instance, in cases where due process principles may potentially be invoked, unless the such standard is conceptually or empirically justified based on irreproachable evidence, it would represent an arbitrary re-allocation of evidentiary standards.
Keywords: Evidence; Comparative Law; Clear Convincing Evidence; Hong Kong